2016
DOI: 10.1111/acer.13119
|View full text |Cite
|
Sign up to set email alerts
|

Binge Drinking Decreases Corticotropin‐Releasing Factor‐Binding Protein Expression in the Medial Prefrontal Cortex of Mice

Abstract: Background Dysregulation of the corticotropin releasing factor (CRF) system has been observed in rodent models of binge drinking, with a large focus on CRF-Receptor 1 (CRF-R1). The role of CRF-Binding Protein (CRF-BP), a key regulator of CRF activity, in binge drinking is less well understood. In humans, single nucleotide polymorphisms in CRHBP are associated with alcohol use disorder and stress-induced alcohol craving, suggesting a role for CRF-BP in vulnerability to alcohol addiction. Methods The role and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 54 publications
5
26
0
1
Order By: Relevance
“…Indeed, the CRF-BP has recently received attention as a potential target for its role in alcohol use disorder (Haass-Koffler et al 2016, Ketchesin et al 2016); and, particularly, its role in the escalation of alcohol drinking may involve interaction with CRF 2 receptors (Albrechet-Souza et al 2015, Quadros et al 2016). Receptor activity modifying proteins (RAMPs) are other molecules that interact directly with the CRF system, as RAMP2 binds CRF 1 and increases its surface expression and signaling sensitivity (Wootten et al 2013).…”
Section: Targeting and Validating Drug Action In Humansmentioning
confidence: 99%
“…Indeed, the CRF-BP has recently received attention as a potential target for its role in alcohol use disorder (Haass-Koffler et al 2016, Ketchesin et al 2016); and, particularly, its role in the escalation of alcohol drinking may involve interaction with CRF 2 receptors (Albrechet-Souza et al 2015, Quadros et al 2016). Receptor activity modifying proteins (RAMPs) are other molecules that interact directly with the CRF system, as RAMP2 binds CRF 1 and increases its surface expression and signaling sensitivity (Wootten et al 2013).…”
Section: Targeting and Validating Drug Action In Humansmentioning
confidence: 99%
“…Wang, You, Rice, & Wise, 2007). The CRF-BP has recently received attention as a potential target for its role in alcohol use disorder (Haass-Koffler et al, 2016; Ketchesin, Stinnett, & Seasholtz, 2016), and its role in the escalation of alcohol drinking may involve its interaction with CRF 2 (Albrechet-Souza et al, 2015; Quadros, Macedo, Domingues, & Favoretto, 2016). Intriguingly, recent gene variant studies in humans have shown that the CRHBP rs1875999 locus was associated with risk for both cocaine and heroin addiction in African Americans in a study of heroin addicts ( n = 314), cocaine addicts ( n = 281), and healthy controls ( n = 208) (Levran, Peles, et al, 2014; Levran, Randesi, et al, 2014).…”
Section: Role For Crf-crf1 Systems In Animal Models Of Addictionmentioning
confidence: 99%
“…This suggests a unique functional neuroadaptation in the CeA following repeated binge cycles that may contribute to escalated alcohol use and maintenance of excessive binge-like alcohol intake. Similar to adolescents, repeated cycles of DID do not alter CRF-ir or CRF mRNA outside the CeA (i.e., in the BNST, BLA, MeA, NAc core and shell, lateral hypothalamus, or lateral septum; Ketchesin et al 2016; Lowery-Gionta et al 2012). Interestingly, the VTA exhibits transient increases in CRF and decreases in CRF-BP levels following acute binge cycles that normalize after repeated binge exposures (Ketchesin et al 2016; Lowery-Gionta et al 2012; Rinker et al 2017).…”
Section: 3 Alcohol Effects On Crf Signalingmentioning
confidence: 90%
“…Similar to adolescents, repeated cycles of DID do not alter CRF-ir or CRF mRNA outside the CeA (i.e., in the BNST, BLA, MeA, NAc core and shell, lateral hypothalamus, or lateral septum; Ketchesin et al 2016; Lowery-Gionta et al 2012). Interestingly, the VTA exhibits transient increases in CRF and decreases in CRF-BP levels following acute binge cycles that normalize after repeated binge exposures (Ketchesin et al 2016; Lowery-Gionta et al 2012; Rinker et al 2017). More specifically, CRF mRNA and CRF-ir in VTA are increased following 1 cycle of DID, but CRF-ir normalizes after 6 cycles of DID (CRF mRNA was not measured after 6 cycles; Lowery-Gionta et al 2012; Rinker et al 2017).…”
Section: 3 Alcohol Effects On Crf Signalingmentioning
confidence: 90%
See 1 more Smart Citation